Enhancing the sine cosine algorithm with swap operator for team formation problem - Kader, Md Abdul; Kamal Z., Zamli; Mekeng, Ambros Magnus Rudolf (Association for Computing Machinery, 2024)
Forming a group of experts who fulfill the requirements of a collaborative endeavor is vital. Aiming to reduce communication costs among the team of experts in their effort to resolve the team formation challenge, this work introduces an enhanced sine cosine algorithm. Improving Sine Cosine Algorithm with a Swap Operator (ESCASO) is the designation given to the proposed method. To augment the diversity of SCA, we employed a swap operator within the sine cosine algorithm. In contrast to other meta-heuristic algorithms such as the grey wolf optimizer, harris hawks optimization algorithm, and traditional sine cosine algorithm, we are evaluating the ESCASO's performance by applying it to the IMDB dataset. Based on the experimental findings, it can be concluded that the proposed algorithm effectively identifies teams that achieve the goal with minimal communication cost among team's members.